Identification and Characterization of (3Z):(2E)-Hexenal Isomerases from Cucumber - Spyropoulou, Eleni A.; Dekker, Henk L.; Steemers, Luuk; van Maarseveen, Jan H.; de Koster, Chris G.; Haring, Michel A.; Schuurink, Robert C.; Allmann, Silke (Frontiers in Plant Science, 2017)
E-2-hexenal is a volatile compound that is commonly emitted by wounded or stressed plants. It belongs to the group of so-called green leaf volatiles (GLVs), which play an important role in transferring information to plants and insects. While most biosynthetic enzymes upstream of E-2-hexenal have been studied extensively, much less is known about the enzyme responsible for the conversion from Z-3- to E-2-hexenal. In this study we have identified two (3Z):(2E)-hexenal isomerases (HI) from cucumber fruits by classical biochemical fractionation techniques and we were able to confirm their activity by heterologous expression. Recombinant protein of the HIs did not only convert the leaf aldehyde Z-3-hexenal to E-2-hexenal, but also (Z,Z)-3,6-nonadienal to (E,Z)-2,6-nonadienal, these last two representing major flavor volatiles of cucumber fruits. Transient expression of the cucumber HIs in Nicotiana benthamiana leaves drastically changed the GLV bouquet of damaged plants from a Z-3- to an E-2-enriched GLV profile. Furthermore, transcriptional analysis revealed that the two HIs showed distinct expression patterns. While HI-1 was specifically expressed in the flesh of cucumber fruits HI-2 was expressed in leaves as well. Interestingly, wounding of cucumber leaves caused only a slight increase in HI-2 transcript levels. These results demonstrate that cucumber (3Z):(2E)-hexenal isomerases are responsible for the rearrangement of Z-3-aldehydes in both leaves and fruits. Future research will reveal the physiological importance of an increased conversion to E-2-aldehydes for plants and insects.